Ammonium removal from water using flow capacitive deionization with MgO-modified biochar derived from orange peels - Mwalusambo, Gabriel; Tarus, Bethwel; Elisadiki, Joyce; Son, Moon; Kim, Hoo Hugo; Jande, Yusufu A. C.; Alfredy, Tusekile (Elsevier BV, 2025)
Ammonium (NH+4 ) in water presents substantial environmental challenges, such as eutrophication and toxicity that necessitate effective removal strategies. This study developed flow electrodes using biochar obtained from orange peels for the removal of NH+ 4 from water through flow capacitive deionization (FCDI). The biochar was prepared through carbonization and modification with MgO at varying ratios using the co-precipitation method. The modified biochar exhibited high hydrophilicity and demonstrated a specific capacitance of 238 F g-1. The FCDI process was optimized at an applied voltage of 1.2 V, an electrode flow rate of 10 mL min- 1 and a 2.5 wt% carbon content in the flow electrode. The modified flow electrodes showed effective performance, attaining an average NH+ 4 removal rate of 17.3 mg m- 2 min- 1, removal efficiency of 86.7 % and retention of 91.3 % after 30 cycles. Notably, the modified MgO flow electrode resulted in approximately 62 % reduction in energy consumption during electrosorption compared to pristine biochar, indicating advantages emanating from reduced solution and charge transfer resistances. Experiments with simulated municipal wastewater confirmed the modified electrode's superior ability, consistent stability over multiple cycles, and selectivity in NH+4 removal. This study highlights the efficacy of the developed flow electrodes for FCDI systems, offering a straightforward electrode synthesis method and effective NH+4 removal.